Decentralizing Civic Learning: The Pedagogical Potential of the Civic Kolaborasik Community as a Third Space for University Students - Tity Kusrina; Ibnu Sulaiman; Zindan Baynal Hubi; Kireida Rona Islam; Hilman Gufron; Tity Kusrina; Ibnu Sulaiman; Zindan Baynal Hubi; Kireida Rona Islam; Hilman Gufron (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
The background of this research is the conflict between the idealism of the Pancasila and Civic Education curriculum and the reality of economic pragmatism in industrial areas, which triggers student apathy and academic burnout due to rigid, one-way learning models. To analyze the role of the Civic Kolaborasik community as a "third place" in activating critical awareness and students' political self-efficacy in the Tegal coastal area, this research employs a qualitative approach with a longitudinal case study design. Data were gathered through in-depth interviews with 18 cross-disciplinary informants, participatory observation, and documentation, then analyzed thematically using NVivo software. The validity and credibility of the findings were ensured through data triangulation techniques to cross-verify various information sources and member checking to verify the consistency of data interpretation with the informants' experiences. The results indicate that Civic Kolaborasik effectively mitigates academic burnout by deconstructing campus hierarchies into an egalitarian learning ecosystem through the implementation of "creative pedagogy" based on local public issues. The synergy between alumni mentoring and cross-disciplinary collaboration has proven capable of transforming the student paradigm from symbolic-reactive nationalism to tangible active-substantive nationalism. Consequently, the internalization of national values through civic inclusivity successfully enhances students' political self-efficacy, allowing them to transform into adaptive agents of change in the face of contemporary disruption challenges.